Social Media as A Political Space in The Digital Age - Mikhael Yulius Cobis; Hafied Cangara (PERSPEKTIF, 2023)
The explosion of digital media has seen the expansion of social media platforms into the lives of many technologically privileged and networked people to new communication environments. When campaign organizations and political parties start to turn their attention to social networking sites. This study aims to analyze the role of social media as a political space in the digital era. This research is descriptive analytic using library research as a source of data and information, which comes from books, academic texts, scientific journal articles, or other literary sources. We conclude by highlighting open questions about how the Internet and social media shape politics in democracies and autocracies. The literature has concluded that in places where the main public complaints are related to corruption, subversion of power, and control of traditional media by autocrats, free internet and social media do increase accountability by informing the public and facilitating the organization of protests. This is why autocrats are increasingly censoring the Internet, banning social media they cannot monitor and flooding with misinformation on social media networks they cannot ban.